ORGANIZATIONAL MAINTENANCE OF DISTANCE LEARNING FOR THE HIGHER PEDAGOGICAL EDUCATION (Journal of Information Technologies in Education (ITE), 2010)
The article deals with the organizational maintenance of distance learning for higher pedagogical education at two basic levels: national level of the organisation of distance learning system and at level of educational process with use of distance learning technologies.
Keywords: distance course; distance learning; distance learning system; higher pedagogical education; organizational maintenance